The Tax Avoidance Clause: Do We Want it, Do We Need it? - Nieborak, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The aim of this paper is to outline the institution of the tax avoidance clause which has recently been re-introduced to the Polish legal system. The clause is known in many legal systems worldwide, and always arouses numerous controversies, which arise primarily from the subjectivity as well as, partly, the retroactivity of its application, which is based on extremely general principles, leaving a vast interpretative margin to the tax authorities enforcing the clause. Selected problems arising from the implementation of the tax avoidance clause in the Polish legal system have been analysed. These theoretical problems will be real once the clause has been enforced.